PENGEMBANGAN GROUP INVESTIGATION DENGAN PERMAINAN “AKU SEORANG DETEKTIF” KELAS IV SD MUHAMMADIYAH 1 MALANG - Renika Arisinta; Bayu Hendro Wicaksono; Ima Wahyu Putri Utami (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2017)
Abstract: The type of research conducted is Research and Development (RnD). In this research aiming to produce product development of Group Investigation(GI) learning modelwith game